TSG-6 expression distinguishes rejected and non-rejected human lung transplants: a retrospective study - Khan, Mohammad Afzal; Li, Dong ge; Zhang, Ashling L.; Krupnick, Alexander S.; Lau, Christine L. (Frontiers in Immunology, 2025)
Lung transplantation (LTx) remains the definitive treatment for select end-stage pulmonary diseases, yet early graft failure due to acute rejection continues to compromise long-term outcomes. Tissue injury and insufficient reparative responses in the immediate post-transplant period contribute to this vulnerability. Tumor Necrosis Factor-Stimulated Gene-6 (TSG-6) is a multifunctional anti-inflammatory and tissue-protective protein known to facilitate resolution of inflammation and extracellular matrix remodeling, but its role in human LTx remains undefined. In this retrospective study, we examined TSG-6 expression in transbronchial biopsies from two matched cohorts of LTx recipients—those with histopathologically confirmed acute rejection (n = 6) and those without rejection (n = 6)—within the first postoperative month. Immunofluorescence analysis revealed significantly elevated TSG-6 expression in non-rejected grafts across two metrics: whole-biopsy staining intensity (Mean 11 ± 1.6 units vs 2.35 ± 0.5, p < 0.01) and percentage of TSG-6–positive cells (~90% vs. ~30%, p < 0.01). Scatter plot visualization confirmed a clear separation between groups, suggesting that elevated TSG-6 expression—both in total tissue and per-cell prevalence—is strongly associated with the absence of acute rejection and may reflect a reparative immune phenotype. Despite the limited sample size, the consistency and magnitude of the effect (Cohen’s d ≈ 4.7) underscore the biological relevance of TSG-6 in early graft stability. Our data establish a novel link between increased TSG-6 expression and diminished acute rejection in human lung allografts, suggesting that TSG-6 may actively modulate alloimmune responses and serve as both a marker of graft stability and a candidate for therapeutic intervention.